Macroscopic electrostatic effects in ATR-FTIR spectra of modern and archeological bones - Aufort, Julie; Lebon, M.; Gallet, X.; Ségalen, L.; Gervais, C.; Brouder, C.; Balan, E. (MINERALOGICAL SOC AMER, 2018)
© 2018 Walter de Gruyter GmbH, Berlin/Boston 2018. Bones mostly consist of composite materials based on almost equivalent volume fractions of mineral (apatite) and organic (collagen) components. Accordingly, their infrared spectroscopic properties should reflect this composite nature. In this letter, we show by theory and experiment that the variability of the strong phosphate bands in the ATR-FTIR spectra of a series of modern and archeological bone samples can be related to electrostatic interactions affecting apatite particles and depending on the bone collagen content. Key parameters controlling the shape of these bands are the mineral volume fraction and the dielectric constant of the embedding matrix. The magnitude of these effects is larger than the one related to microscopic changes of the apatite structure. Consequently, the interplay of microscopic and macroscopic parameters should be considered when using FTIR spectroscopy to monitor the preservation state of bioapatite during diagenetic and fossilization processes, especially during the degradation of the organic fraction of bone.